2015
DOI: 10.3354/meps11058
|View full text |Cite
|
Sign up to set email alerts
|

Are bio-telemetric devices a drag? Effects of external tags on the diving behaviour of great cormorants

Abstract: Externally attached remote-sensing devices used to study animals in their environment are a possible source of disturbance, notably in terms of drag, for diving species. The aim of the present study was to assess the possible effect of device-induced drag on the diving performance of great cormorants Phalacrocorax carbo. Based on wind-tunnel measurements, we assessed the effect of device size on drag and derived a formula to predict how drag changes as a function of both swim speed and device cross-sectional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 68 publications
1
39
0
Order By: Relevance
“…The power required to overcome drag (P) is given by P = 0.5 A Cd v 3 ρ, where A is the cross-sectional area of the animal, Cd is the drag coefficient, ρ is the density of the fluid medium and v is the velocity. Thus, although our attached device would increase the drag by increasing the cross-sectional area marginally, it is the swim speed that is going to be a prime modulator of increased energy expenditure (Vandenabeele et al 2015). Importantly, work by Vandenabeele et al (2015) showed that up to speeds of 1.5 m/s, the energy consumption of a tag-fitted great cormorant Phalacrocorax carbo was unlikely to differ much from the untagged conspecific, but that differences between them accelerated quickly thereafter.…”
Section: Dragmentioning
confidence: 91%
See 2 more Smart Citations
“…The power required to overcome drag (P) is given by P = 0.5 A Cd v 3 ρ, where A is the cross-sectional area of the animal, Cd is the drag coefficient, ρ is the density of the fluid medium and v is the velocity. Thus, although our attached device would increase the drag by increasing the cross-sectional area marginally, it is the swim speed that is going to be a prime modulator of increased energy expenditure (Vandenabeele et al 2015). Importantly, work by Vandenabeele et al (2015) showed that up to speeds of 1.5 m/s, the energy consumption of a tag-fitted great cormorant Phalacrocorax carbo was unlikely to differ much from the untagged conspecific, but that differences between them accelerated quickly thereafter.…”
Section: Dragmentioning
confidence: 91%
“…Thus, although our attached device would increase the drag by increasing the cross-sectional area marginally, it is the swim speed that is going to be a prime modulator of increased energy expenditure (Vandenabeele et al 2015). Importantly, work by Vandenabeele et al (2015) showed that up to speeds of 1.5 m/s, the energy consumption of a tag-fitted great cormorant Phalacrocorax carbo was unlikely to differ much from the untagged conspecific, but that differences between them accelerated quickly thereafter. Thus, since beavers generally swim between 0.8 m/s on the surface (Nolet and Rosell 1994) and 0.6 m/s when submerged (Allers and Culik 1997), we would not expect drag-based power to compromise the animals greatly.…”
Section: Dragmentioning
confidence: 91%
See 1 more Smart Citation
“…Tags deployed in capture-release programs (Moore et al, 2016) are typically placed in this preferred position; however, pole-based deployments on cetaceans of any size lead to attachments in any orientation or location. Tags placed on different regions of the body may have considerably different hydrodynamic regimes and will therefore contribute different drag and lift forces and pitching moments: when placed ahead of the point of maximal girth tags can lead to early flow separation and large increases in frontal area , but those placed too far caudally can result in body destabilization (Culik and Wilson, 1991;Healy et al, 2004;Vandenabeele et al, 2015). Suction cup tags such as the DTAG can slide into a new position or orientation as drag forces over the tag exceed suction forces in the cup holding it to the animal (Moore et al, 2016).…”
Section: Simulated Measured and Natural Speedsmentioning
confidence: 99%
“…However, this is only one factor to consider during tag development, especially with respect to affecting the behaviour, physiology or demography of the animal [20,21]. Tag weight has received a lot of attention, especially in flying or diving animals [40,41]. It is generally agreed that tag weight should be <5 % (or <3 % as recently proposed) of the body weight of the animal [42][43][44].…”
mentioning
confidence: 99%